2015
DOI: 10.6018/analesps.31.3.192041
|View full text |Cite
|
Sign up to set email alerts
|

Examining the predictive role of self-compassion on flourishing in Turkish university students

Abstract: Título: Examen del papel predictivo de la autocompasión sobre el bienestar psicológico (flourishing) en estudiantes universitarios de Turquía. Resumen: El propósito de este estudio es examinar el papel predictivo de la autocompasión sobre el flourishing. Los participantes fueron 278 estudiantes universitarios (153 mujeres, 125 hombres; edad media = 20.5 años). En este estudio, la Escala de Autocompasión y la escala de Flourishing fueron examinadas usando análisis correlacional y análisis de regresión lineal mú… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 35 publications
10
40
0
7
Order By: Relevance
“…The second finding of the study showed that as self-compassion increases, selfhandicapping decreases. This finding was supported by previous studies (Akın & Akın, 2015;Petersen, 2014). The negative correlation between these two variables can be explained by approaching the failure situation and evaluation anxiety (Rhodewalt et al, 1991;Neff et al, 2005).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The second finding of the study showed that as self-compassion increases, selfhandicapping decreases. This finding was supported by previous studies (Akın & Akın, 2015;Petersen, 2014). The negative correlation between these two variables can be explained by approaching the failure situation and evaluation anxiety (Rhodewalt et al, 1991;Neff et al, 2005).…”
Section: Resultssupporting
confidence: 89%
“…Self-compassion is required not only to accept the self as a whole with both positive and negative features but also to behave more compassionate to the self in case of negative life experiences (Neff et al, 2005). There are limited number of studies that examine the predictor role of selfcompassion in explaining self-handicapping and these studies found a negative correlation between two variables (Akın & Akın, 2015;Petersen, 2014) Being another predictor in the study, academic self-efficacy is considered as an important factor in explaining self-handicapping. It represents the belief of accomplishing an academic task (Britner & Pajares, 2006).…”
Section: Extended Summarymentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have demonstrated that self-compassion is an indicator of psychological health, with higher self-compassion being associated with greater psychological well-being (Akin & Akin, 2015;Neff, Rude, & Kirkpatrick, 2007) and less depression, anxiety, and stress (Krieger, Altenstein, Baettig, Doerig, & Holtforth, 2013;MacBeth & Gumley, 2012;Neff, 2003a). More recently, some studies have sought to understand the relationship between self-compassion and cognitive processes.…”
mentioning
confidence: 99%